Qualitative research in the area of TEL - Parmaxi, Antigoni (My University, 2026)
This Qualitative Research module will mainly introduce participants to Qualitative Research and Computer-Assisted Qualitative Data Analysis (CAQDAS) through the use of NVivo, a software program used for qualitative and mixed-methods research. It will be divided into two main parts, starting with a general theoretical introduction on Qualitative Research and moving on to the more practical part, in which participants will be provided with the opportunity to attend a demonstration of entering and coding qualitative data. Initially, prior to the workshop, participants will be provided with some pre-reading and pre-viewing material, through which they will be informed about the specific software, NVivo, and they will be given instructions as to how to install it on their device, so as to prepare for the synchronous workshop. During the synchronous workshop, the trainer(s) will firstly provide a brief introduction to Qualitative Research theory, key considerations of Qualitative Data Analysis (QDA) and then describe how CAQDAS can support QDA. The basic features of NVivo will then be demonstrated, focusing on how it can be used for entering and coding data mainly yielded from interviews, pdf, surveys, websites, among others.